STUDY ON THE VERTICAL DISTRIBUTION OF CHLOROPHYLL IN COASTAL OCEAN; DEVELOPMENT OF VERTICAL MODEL FUNCTION AT WESTERN SUMBAWA SEA - Dati Pertami, Nyoman; Kanno, Susumu; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 1 No 2, 2012)
The primary production quantity depends on the vertical distribution of chlorophyll concentration inthe water column. The chlorophyll maximum value not always observed near or at the sea surface, butsometimes lies deeper than bottom of the euphotic zone. In this case, the ocean color sensors cannot measurethe chlorophyll maximum value. Vertical distribution of chlorophyll modeled and calculated withdevelopment of Vertical Model Function (VMF) by “Gaussian function”.This research has been carried out in western area of Sumbawa Sea. There were 178 stations of fieldobservations. The data were collected at each 0.5 m depth up to 200 m sea depth. Results processing ofprimary data, with correlations between chlorophyll concentration and depth in every station can show typesof vertical distribution of chlorophyll in all stations. There are five types of vertical distribution ofchlorophyll at Western Sumbawa Sea. The” five types” then classified into two main groups namely areLinear (L) type and Gaussian (G) type. Finally, data were processed to obtained one especially type that is“one type”. The regression analysis was carried out on the parameters in the Gaussian Function, BO, S, h, ?and Zmax for the each type of the vertical distribution of chlorophyll concentration.Vertical distribution of chlorophyll found at Western Sumbawa Sea are Linear (L) type, Linearsurface (LS) type, Gaussian (G) type, Gaussian with maximum surface (GS) type, and Linear with maximumsurface (LMS) type, where with “five types” have nine coefficient determinants (R) which below than 0,25.The regression analysis were modified from “five types” into “two types” and the result was two coefficientdeterminants (R) that below than 0,25. Correlation coefficient with “one type” have better result than theother types which has only one coefficient determinant (R) that below than 0,25.
Keywords: Vertical distributions, Chlorophyll, Gaussian function